He He :)
Had me thinking for sometime!
But the answer is darnedly simple:
9/2 = 4.5
So, 4 - 9/2 = 4 - 4.5 = -0.5
And, 5 - 9/2 = 5 - 4.5 = 0.5
And (-0.5)^2 = (0.5)^2. But this does not mean: -0.5 = 0.5
You cannot equate squares directly like that. Whenever u equate two squares, always a "plus or minus" comes into the picture!
i.e., if a^2 = b^2, then it DOES NOT mean a = b.
It means: a = plus or minus b. (a = b OR a = -b)
2006-11-08 15:18:34
·
answer #1
·
answered by Flashy V 2
·
0⤊
0⤋
There is no error: the two expressions are actually equal.
4 - 9/2 = -1/2
5 - 9/2 = 1/2
Squaring both of these gives the same result.
2006-11-08 15:12:42
·
answer #2
·
answered by Clueless 4
·
1⤊
0⤋
There is no error because
(4-9/2)*(4-9/2)=1/4
and
(5-9/2)*(5-9/2)=1/4
both r equal
2006-11-08 18:44:52
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
The error is that you can't take 5and subtract9 and you can't take16 and- 36 25-45is imposslible.5-9/20is nothing because it is 5-18.
There is a lot of errors in this too much too point out .
2006-11-08 15:17:19
·
answer #4
·
answered by Maddie G 2
·
0⤊
0⤋
when you take square root therecan be two values +/-
only one of the values may satisfy the equation
also (a-b)^2=(b-a)^2
like in this case
rt of(4-9/2)^2=>rt of(9/2-4)^2=1/2
rt of (5-9/2)^2=1/2
so 9/2-4=5-9/2
which is correct
2006-11-08 15:10:49
·
answer #5
·
answered by raj 7
·
0⤊
0⤋
16-36=25-45
16-36+81/4=25-45+81/4
(1-9/2)*(4-9/2)=(1-9/2)*(5-9/2)
2006-11-08 16:47:47
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
very simple.. see the folloing
4 - 9/2 = -0.5
5 - 9/2 = 0.5
and this is resulting is diffence of 1
2006-11-08 15:21:49
·
answer #7
·
answered by doctor4allfammy 2
·
0⤊
0⤋
i have lost i could not find error.
there is n error
i) -20 = -20 (is true)
ii) -20+81/4 = -20+81/4
=> (-80+81)/4 = (-80+81)/4
=> -1/4 = -1/4 (is true )
iii) (4-4.5) * (4-4.5) = (5-4.5) * (5-4.5)
=> -0.5 x -0.5 = 0.5 x 0.5
implies 0.25 = 0.25 again its true
.where did u get 4=5 dear please tell me i wanna know
2006-11-08 15:48:20
·
answer #8
·
answered by The Prince of Egypt 5
·
0⤊
0⤋
16=20 u fool.
2006-11-08 22:44:29
·
answer #9
·
answered by varun 2
·
0⤊
0⤋
square of (-a) is a^2
square of (+a) is also a^2
whether we can say (-a) equals to (+a)
If it is true, the following example will clear ur doubt
Suppose you have given Rs.'a' to me as a loan
For repayment, you only have to give me Rs. 'a'
2006-11-08 17:19:57
·
answer #10
·
answered by dondon 2
·
0⤊
0⤋